IDE614 : Furniture innovation design I / College of Creative Arts - UiTM, College of Creative Arts (Universiti Teknologi MARA (UiTM), 2023)
As a final year semester the module will be self-directed. The lecturer appears here as a facilitator. Study groups will be formed to collect and share data and research findings. From the ‘chosen self-interest project’ on furniture, a broader aspect of creativity and problem solving will be explored through design. The process development will involve both, the theory and practice. The understanding on research technique and related issues become the focal attention in ensuring the student competency in integrating the project intention, problem identification and outcomes expectation. This course aims to prepare students for developing their understanding in Product Research and Development. This course will give students capability to apply their knowledge in Research Methodology to understand the needs of user in terms of product performance, usability, manufacture and aesthetic. Information that gathered from the research have to analyze by the students and develop a product that have the features to solve the problems of current products in the market. This course is designed to educate students about the process of data collection, research method, data analysis and design a product that look at problems differently to provide innovative solutions.